STRUKTUR DAN KOMPOSISI JENIS MANGROVE DI DESA BANGKIR KECAMATAN DAMPAL SELATAN KABUPATEN TOLITOLI - Setiawan, Aan; Korja, I Nengah; Sustri, Sustri; Naharuddin, Naharuddin; Toknok, Bau; Rukmi, Rukmi (Universitas Tadulako, 2021)
The existence of mangrove vegetation in Bangkir Village, Dampal Selatan District, Tolitoli Regency has decreased due to the conversion of mangrove forests into ponds. This study aims to determine the structure and composition of mangrove species in the village of Bangkir. This study uses two methods, namely the qualitative descriptive method through the survey method and the line transect method. Determination of the transect line amounted 1 line and plot placement by purposive sampling amounted to 6 plots. Parameters salinity, pH and soil texture. Data analysis was performed by calculating the relative density, relative frequency and relative dominance to obtain the Importance Value Index (IVI). The results showed that the forest structure consists of three layers, namely layer C and D which are dominated by Avicennia marina, layer E is dominated by Bruguiera cylindrica, while the type Sonneratia alba does not dominate the three layers. The composition the types of constituents are 3 types of mangroves and 3 families. The species that had the highest Importance Value Index (IVI) at all growth stages trees, saplings and seedlings was Avicennia marina and the lowest was Sonneratia alba. The growth salinity level Avicennia marina species has a salinity of 38%, then a pH of 5.14-6.18, the soil texture is a dusty clay substrate, the Sonneratia alba species has a salinity level of 33%, a pH of 5.20-6.62, the texture of clay sand, and Bruguiera cylindrica species have a salinity level of 26%, pH 6.17-7.23, texture of clay substrate.Keywords: Structure, Composition, Mangrove